Effects of a financial capability intervention program on financial wellbeing of medical practitioners in Selangor, Malaysia - R.Anthony, Rajna (2018)
The practice of medicine though rewarding is extremely demanding and stressful. With such high level of stress, compounded by poor work-life balance, many medical practitioners fail as competent money managers. In today's financial market, the financial service sector has created more accessible and greater financial services that require smart decision making interactions. This expectation has heightened the requirement for a financial capability intervention program on the financial wellbeing of the medical practitioners. This study adopted a sequential explanatory mixed methodology with randomized controlled pre-test-post-test experimental design. The Family Resource Management Model and the Financial Capability Model were integrated into a Logic Model Framework to serve as the proposed research conceptual framework. The Theory of Planned Behaviour and the theory of Transtheoretical Model of Behaviour Change were utilised to measure the outcome effect and to identify the Stages of Behavior Change of the participated medical practitioners before and after a financial capability intervention program. A total of 100 medical practitioners were randomly assigned into intervention and control groups in equal proportion after both groups completed the pre-test questionnaire. The intervention group participants attended a series of five two hour one on one coaching session while the control group did not. After a four-month duration both the groups completed the post evaluation (post-test). In-depth interviews were conducted on seven selected participants based on criterion sampling. Parametric statistical techniques and thematic analysis were used to analyse the quantitative and qualitative data respectively.Impact indicators revealed statistically significant increase in the levels of financial knowledge (30%), skill (24%), confidence (9%), practice (20%), financial capability (20%) and financial wellbeing (20%). There was also large magnitude of change (on Cohen’s interpretation) in the effect sizes of within subject (pre and post) and between subjects (intervention and control) of financial knowledge (d=2.15), skill (d=2.53), practice (d=1.960), financial capability (d=2.4) and financial wellbeing (d=1.68) whereas financial confidence showed medium effect (d=0.63). The control group did not show any significant changes. No significant relationship was found between financial knowledge and financial wellbeing as well as between financial skill and financial wellbeing of the medical practitioners before and after the intervention program. However, financial confidence, financial practice, and overall financial capability showed positive linear correlation with financial wellbeing. Significant desirable positive financial behaviour stages of change were found in managing money, planning ahead, making choices and staying informed domains between those medical practitioners who were coached (intervention group) and those who were not (control group). The pre-test and post-test data of the control group showed that their financial behavioral stage remained unchanged. Alternat ively, the medical practitioners who attended the four-month coaching program showed a distinct forward movement from one financial stage to another. The findings of this study have implications for policy makers, financial educators, financial counsellors and coachers, workplace administrators, financial planners and medical practitioners themselves. Similar to coaching sport athletes, financial coaching have implications to enhance financial capability by building financial confidence. Hence, strategic financial activities for healthcare workers by opening staff financial wellness resource centres in the hospital to give coaching and counselling need to be considered. It is recommended that prior to designing appropriate financial literacy initiatives and undertake policy interventions it is vital for policy makers to understand consumer behavior and identify their weak financial areas based on initial assessment. Collaborative public-private partnership to drive financial capability programme at national level as an essential life skill from early age to adulthood is recommended. Finally, financial capability intervention programmes need to be promoted and complemented with coaching and counselling with regular follow up to motivate behaviour change. In summary, this financial capability intervention program effectively brought about significant positive effect on the financial capability of the medical practitioners and subsequently on their financial wellbeing. As such, a logic model framework for financial capability intervention program was proposed through this study. Hence, this financial capability intervention program sets groundwork and stronger foundation for future research among other target population.